Investigating How Policies and Other Conditions Contribute to Influencing Agricultural GHG Emissions in the EU - Francesco Galioto; Irene Criscuoli; Andrea Martelli; Maria Valentina Lasorella; Ilaria Falconi; Danilo Marandola; Giovanni Dara Guccione; Francesca Varia (Land)
The present study aims at investigating the potential impacts of agricultural policies on GHG emissions from agriculture across the European Union. The study begins by providing evidence on how the key CAP reforms contributed to the structural changes the European agriculture faced in the past. Based on these facts, we introduce the context of implementation of the 2014–2022 Common Agricultural Policy (CAP), within which many interventions were designed to improve sustainability and increase competitiveness, and we formulate hypotheses on how CAP instruments can contribute differently to influencing GHG emissions from agriculture. The hypotheses formulated concern the following: (1) the influence of the income support payment on land prices and, consequently, on land distribution between small and large landowners; (2) the influence of the coupled payment on agricultural specialization; (3) the influence of agri-environmental-climate measures on the sustainable management of agricultural lands. These causalities can have direct and indirect effects on GHG emissions from agriculture. The method of qualitative comparative analysis (QCA) is used to investigate the above-mentioned causalities and to cluster observations based on similar combinations of conditions (i.e., drivers) and outcomes (i.e., positive or negative variations in GHG emissions from agriculture between the end and the beginning of the CAP programming period). The results reveal that the increase in GHG emissions from agriculture over the study period is mainly attributable to the low share of agricultural land under management contracts targeting climate change mitigation and carbon sequestration through the CAP. CAP payments coupled with production were found to contribute to further increasing GHG emissions from agriculture in some eastern and northern EU countries. Livestock concentrations, income support payments and the high price of agricultural land drive the increase in GHG emissions for other central and eastern EU countries. The paper concludes by addressing existing shortcomings due to conflicting interventions in the current CAP strategic plans.